Uncertainty Principle for Gabor Transform on the Quaternionic Heisenberg Group. (27th July 2021) - Faress, Moussa; Fahlaoui, Said
Abstract: In this paper, we recall the main results of the Fourier transform on the quaternionic Heisenberg group, then we introduce the notion of the Gabor transform on this group and study some of its properties. Finally, we prove some uncertainty principles associated with this transform.